2023
DOI: 10.1093/europace/euad183
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five years of research in cardiac imaging in electrophysiology procedures for atrial and ventricular arrhythmias

Antonio Berruezo,
Diego Penela,
Beatriz Jáuregui
et al.

Abstract: Catheter ablation is nowadays considered the treatment of choice for numerous cardiac arrhythmias in different clinical scenarios. Fluoroscopy has traditionally been the primary imaging modality for catheter ablation, providing real-time visualization of catheter navigation. However, its limitations, such as inadequate soft tissue visualization and exposure to ionizing radiation, have prompted the integration of alternative imaging modalities. Over the years, advancements in imaging techniques have played a pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 138 publications
0
3
0
Order By: Relevance
“…The use of pre-procedural cardiac imaging is increasingly supported by scientific evidence for accurate diagnostic classification, prognostic stratification, and peri-procedural support. 25–28 In all patients, a pre-procedural MDCT was obtained with a Revolution™ CT scanner (General Electric Healthcare). The images were acquired during an inspiratory breath-hold using retrospective ECG-gating technique with tube current modulation set between 50% and 100% of the cardiac cycle.…”
Section: Methodsmentioning
confidence: 99%
“…The use of pre-procedural cardiac imaging is increasingly supported by scientific evidence for accurate diagnostic classification, prognostic stratification, and peri-procedural support. 25–28 In all patients, a pre-procedural MDCT was obtained with a Revolution™ CT scanner (General Electric Healthcare). The images were acquired during an inspiratory breath-hold using retrospective ECG-gating technique with tube current modulation set between 50% and 100% of the cardiac cycle.…”
Section: Methodsmentioning
confidence: 99%
“…In the last few years, the use of pre-procedural cardiac imaging is increasingly supported by scientific evidence for accurate diagnostic classification, prognostic stratification, and peri-procedural support for the ablation of arrhythmias. 9–13 It has been recently shown that pre-procedural multidetector computed tomography (MDCT)-derived images can be used to obtain 3D LAWT maps. 8 , 14 Integrating these LAWT maps into the navigation system provides a real-time knowledge of the local LAWT in contact with the ablation catheter tip during the ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Premature ventricular contraction (PVC) is a frequent cardiac arrhythmia 1 and numerous electrophysiological causes have been proposed to explain PVC occurrence 2 , 3 . However, the exact mechanistic origin of PVCs is unclear and the development of cardiac imaging particularly with cardiovascular magnetic resonance imaging (CMR) 4 has shown that PVCs can be associated with underlying substrate abnormalities only diagnosed with CMR.…”
mentioning
confidence: 99%